Ways for copter drone acustic detection - Vilimek, Jakub; Burita, Ladislav (2017 International Conference on Military Technologies (ICMT), 2017)
The article describes the options of passive detection of Unmanned Aerial Systems (UAS), which are not a subject of the X supplement published by Civil Aviation Authority of the Czech Republic. The beginning of the article contains analysis of basic UAS characteristics in acoustic area. In this part some systems for UAS detection using acoustic methods are mentioned. The following part of the article is dedicated to measuring of acoustic indications of the UAS flight and their evaluation. The main part is focused on design of algorithm for UAS detection and its real-time adaptability. The final part of the article evaluates the parameters of previously mentioned algorithm and opportunities for improvement. The paper contains graphical outputs and results of signal processing in MATLAB environment.